ISOLATION AND PRESENCE OF ANTIMALARIAL ACTIVITIES OF MARINE SPONGE Xestospongia sp. - Murtihapsari Murtihapsari; Apriani Sulu Parubak; Bertha Mangallo; Wiwied Ekasari; Puji Budi Asih; Ayu Indah Lestari (Universitas Gadjah Mada, 2013)
Plasmodium falciparum, the agent of malignant malaria, is one of mankind's most severe scourges, mainly in the tropic world. Efforts to develop preventive vaccines or remedial drugs are handicapped by the parasite's rapid evolution of drug resistance. Here, we presented an advance work on examination of antimalarial component from marine life of Xestospongia sp., the study is based on hexane extraction method. The premier result, we obtained five fractions. Among these five fractions, the fourth has the most potent inhibitory against the growth of P. falciparum 3D7 with an IC50: 7.13 µg/mL. A compiled spectrum analysis, FTIR, 1H-NMR and GC-MS, revealed that the fourth fraction consisted abundantly of two secondary metabolites such as flavonoids and triterpenoids. Finally, our results suggest a plausible structure rooted to the base of ibuprofen.